(untitled) (Linguostylistic Studies, 2017)
This article highlights the phenomenon of term synonymy in the Polish ecological terminology. The author generalizes theoretical approaches of the Polish and Eastern-Slavic linguists to the intepretation of the synonymy in the terminological systems and argues the benefits and negative consequences of their use. The study has identified the principal types of the ecological terminological synonyms. More than 2,000 of Polish ecological synonymous terms have been extracted from a standard dictionary and analyzed from the standpoint of the number of synonyms in the synonymic row, the structure of every synonym in the row, their etymology and appropriateness. The semantic approach is defined as the main approach in describing synonyms in the Polish ecological terminology. In terms of the semantic relationships the author classifies them into two groups: terms equal both in meaning and functions and terms equal only in the specific context; according to their origin the synonyms are grouped into genuine Polish terms and borrowed units. Polish ecological terminology contains many Latin and English terms. In accordance with Waniakowa’s classification the term synonyms can be classified into lexical, morphological and syntactic synonymous terms (76% of them are not multi-component terms). The key findings of this study provide basis to conclude that a systemic analysis of synonymous terms used to label ecological units allows structuring the concept field, specifying the professional study terminology and providing context appropriateness of the term.